UJI AKTIVITAS ANTI BAKTERI ASAP CAIR YANG BERASAL DARI BATANG KAYU MANIS DAN KULIT KACANG TANAH - Yefrida -; Farrah Aprilina; Indri Ticel Leone; Refilda - (Universitas Andalas, 2009)
ABSTRAK Antibacterial agent is a compound that prevent the growth and reproduction of bacteria. Antibacterial activity of liquid smoke is caused by acid and fenolic compound. In this research, we determined antibacterial activity of liquid smoke from stem sweet wood and nut shell by using diffusion method. Both of liquid smoke have antibacterial activity to Staphylococcus aureus Eschericia coli population. Their activity almost the same to chloramphenicol, but less than formalin. Keywords : antibacterial activity, liquid smoke, diffusion method